COVID-19 and the decline of autonomy: contact tracing in the age of surveillance capitalism - Manne, Stephanie (Department of Political Studies, 2023)
To develop successful COVID-19 pandemic response models, governments and policy makers are expanding on the known means of public health surveillance by collaborating with privately owned corporates and implementing new forms of surveillance technology, namely, contact tracing applications. This study examines the long-standing history of surveillance as well as the shifts in public health surveillance with the rise in technologically mediated solutions. In both research and public discourse, the overriding conversation is around the preservation of democracy and human rights and fearing the loss of “freedom” to the adoption of COVID-19 surveillance technologies. After analysing a series of academic journals and news articles that have been published since the beginning of the pandemic, this study highlights how a widespread use of such technologies has been encouraged in the name public health and safety, despite existing evidence of the shortfalls of contact tracing applications. By understanding the fundamental failures of democracy and the inequality that it perpetuates, this study argues that in the same way that the COVID-19 pandemic requires the creation of safe and unsafe bodies, so too does the system of democracy which depends upon creating fear and insecurity so that a reliance on the state is strengthened. As a result, the COVID-19 pandemic is accelerating a world of technological solutionism and surveillance that yields very unequal social, political and economic power dynamics wherein biology and personal data are exploited and commodified. This study employs of the theoretical frameworks of Foucault in making sense of the politics behind pandemic response models and the guiding roles of power, governmentality and biopower. While outlining the dangers of surveillance capitalism, this study makes sense of the push to rely on and preserve the system of global capitalist democracy.